استخدام نموذج Springate للتوقع بالفشل المالي لادارة المخاطر المالية للمؤسسة - دراسة حالة مؤسسة صناعية للنسيج - - غربي, سهام; كبوط, عبد الرزاق (جامعة الوادي - University of Eloued, 2022)
The study aimed to test the possibility of using financial analysis tools, represented by weighted financial ratios within the framework of the springate model to predict financial failure, which is considered a financial risk that threatens the institution's progress. And then give a perception about the financial position of the institution in terms of financial risks, and this study was reached by relying on the financial statements for the period from 2013 to 2020 for the Industrial Textiles Corporation. To confirm the ability of the springate model to predict the financial failure of the institution under study, and then the possibility of using it to study the financial risks of the institution
Financial risk management using the Springate model to predict the financial failure of the corporation: Study of the Industrial Textiles Corporation
مقال
Keywords: ادارة المخاطر المالية ; التحليل المالي ; الفشل المالي ; النسب المالية